Risk Factor Analysis of Hypertension in Adolescents in Banjar City - Yuningsih, Aneng; Suprapti, Betty; Kurnia, Anih; Gustiani, Mia Ruhmiati; Asparina, Arina; Ismawi, Ade Sayid; Purnama Sari, N. Jihan Audiya (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Background: The prevalence of hypertension among adolescents is increasing at an alarming rate, especially in Indonesia, driven by modern lifestyle changes and unhealthy dietary habits. Objective: This study aims to identify and analyze lifestyle-related risk factors contributing to hypertension among adolescents in Banjar City, West Java. Methods: A cross-sectional quantitative study was conducted involving 286 adolescents aged 13-18, selected using random sampling. Data were collected via an online questionnaire and analyzed using descriptive statistics, chi-square tests, and binary logistic regression. Results: A total of 70.6% of respondents were categorized as high-risk and 11.9% as very high-risk for hypertension. Significant contributing factors included late-night eating habits (OR=4.85; p<0.005), consumption of high-sodium processed foods (OR=2.48; p<0.005), and inadequate water intake (OR=1.97; p<0.05). Conclusion: Unhealthy lifestyle patterns particularly poor eating and hydration habits are major determinants of adolescent hypertension. School and family-based interventions are essential to instill healthy behavior from a young age.